G430(P) Research and development approval timelines for an NIHR portfolio adopted multicentre observational study in England and Wales. (7th April 2014) - Okike, IO; Anthony, M; Ninis, N; Heath, PT
Abstract : Over the last 15 years the processes for obtaining research and development (R&D) approval for conducting multicentre medical research in England have undergone some changes. The introduction of participant identification centre (PICs) which are organisations from which clinicians or clinical units refer potential participants to a research team based in another organisation, for assessment and possible recruitment to a study is relatively new. Approval is done using the NIHR Coordinated System for gaining NHS permission (CSP). We therefore aimed to evaluate the delay in the R&D approval for an NIHR portfolio adopted observational multicentre study in England and Wales. Methods: The number of working days taken from application to the granting of R&D approval for our study of assessment of healthcare delivery in the management of bacterial meningitis in infants <90 days of age with ethical approval were prospectively recorded. Ethics approval was by Cambridgeshire 2 REC (Ref: 10/H0308/64). Results: R&D approval was obtained from 92 acute NHS Trusts in England and 7 health boards in Wales. In England, 38 (41%) of the NHS Trusts were from the North, whilst Midlands and East of England, London and integrated region and South of England each had 18 (20%). The median working days (excluding all holidays) between application and research governance approval was 57 working days (interquartile range 38–85, range 9–265). This time to approval was similar between the NHS Trusts in England and the Health boards in Wales. However, within England this median time (IQR) varied by geographical areas, 46 days (31–61), 68 days (38–84) and 73 days (44–118) and 74 days (50–113) for the North of England, London and integrated region, South of England and Midlands and East of England respectively (p = 0.007). Conclusions: Our median working time to approval was higher than that for the Study of Outcome of Childhood Stroke in 2008 (43 days, IQR: 27–62) done in the South of England. There is still a considerable delay in the time taken by R&D to grant approval for a research ethics committee approved multicentre observational study. This subsequently leads to significant delays in commencing and completion of such study. Any improvements to the existing systems for gaining approval are welcome.